Research on the spatial layout optimization strategy of Huaihe Road Commercial Block in Hefei city based on space syntax theory - Zhou, Qinghua; Zheng, Yiran (Frontiers in Computational Neuroscience, 2023)
Commercial block not only serves as a public space for the consumption, entertainment, and recreation of residents but also witnesses the history of urban commercial development. With the urban development and the improvement of people’s living standards, most commercial blocks are faced with such problems as traffic congestion, simple commercial form, and unreasonable spatial layout. By taking the commercial block of Huaihe Commercial Pedestrian Street as an example and combining the axis and viewshed analysis method of space syntax theory, this article has analyzed the space and quantified the relevant data to analyze the spatial layout relationships of commercial blocks. As the outcomes, this article summarizes the strategies for optimizing the traffic space, scenic space, and commercial space of commercial blocks, hoping to facilitate the commercial block space layout optimization in the era of stock.